Citizen Satisfaction Improving Government Performance, Efficiency, and Citizen Trust - Morgeson, Forrest V.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Citizen Satisfaction investigates the topic of satisfaction with government services from a variety of perspectives, using case studies and empirical results from satisfaction studies at the federal level.
Keywords: Science; Science; Science, general